Comparison of MALDI-TOF MS With HPLC and Nucleic Acid Sequencing for the Identification of Mycobacterium Species in Cultures Using Solid Medium and Broth. Issue 1 (1st January 2014) - Buchan, Blake W.; Riebe, Katherine M.; Timke, Markus; Kostrzewa, Markus; Ledeboer, Nathan A.
Abstract: Objectives: The genus Mycobacterium contains over 150 species including pathogenic and nonpathogenic strains. Accurate species level identification can aid in differentiating environmental contamination from true infection, and also can aid in selection of antimicrobial therapy. Methods: We evaluated the performance of matrix-assisted laser desorption/ionization time-of-flight mass spectrometry (MALDI-TOF MS) for the routine identification of clinical isolates of mycobacteria using 2 commercially available spectral reference libraries, and also assessed the impact of mycobacterial culture using solid medium and broth on MALDI-TOF MS–based identification. Results: All results were compared with those obtained on high-pressure liquid chromatography and nucleic acid sequencing. Optimal results were obtained with a mycobacterium-specific reference library (Mycobacterium Library v1.0). The identification rate was 89.8% (79/88) for isolates cultured on solid medium and 98.8% (85/86) for isolates analyzed directly from broth. Among these, the proportion identified with a high confidence level was 50.0% (44/88) for isolates cultured on solid medium and 80.2% (69/86) for isolates cultured in broth. Conclusions: Agreement with nucleic acid sequencing for species present in Mycobacterium Library v1.0 was 97.6% (81/83) for isolates cultured on solid medium and 97.5% (79/81) for those cultured in broth.